Selectivity of Benzyl Hydroxamic Acid in the Flotation of Ilmenite - Li, Lixia; Zhang, Chen; Yuan, Zhitao; Liu, Zhichao; Li, Chunfeng (Frontiers in Chemistry, 2019)
The selectivity of benzyl hydroxamic acid (BHA) and the adsorption mechanism of oleate and BHA on ilmenite were systematically investigated using the flotation test and density functional theory (DFT). The flotation test showed that BHA had good selectivity to ilmenite. In the DFT study, the calculated interaction energies and Mulliken population verified the favourable adsorption of oleate and BHA on the ilmenite surface. The results indicated that covalent bonds formed between oleate and ilmenite and that a five-membered ring formed between BHA and ilmenite. The strong selectivity of BHA was due to abundant adsorption sites and solid adsorption of five-membered rings. The present investigation has important implications for further studies of BHA, and will be helpful for screening and designing collectors for ilmenite flotation.